Typhoid and the military in the early 20th century - Gradmann, Christoph; Harrison, Mark; Rasmussen, Anne (Clinical infectious diseases, 2019)
BACKGROUND: In the decades following the discovery of the bacillus causing typhoid, in 1880, understanding of the disease formerly known as enteric fever was transformed, offering new possibilities for prevention. Gradually, measures that aimed to prevent infection from human carriers were developed, as were inoculations designed to confer immunity against typhoid and paratyphoid fevers. These were initially introduced in European armies that were regularly ravaged by typhoid, especially garrisons stationed in the colonies. This article reviews the research undertaken in the armed forces and the measures that they implemented in the years up to and during the First World War. METHODS: The article is based on an analytical review of scientific literature from the early 19th century, focusing on the United Kingdom, Germany, and France. RESULTS: The armies of the United Kingdom, Germany, and France undertook important work on the transmission of typhoid in the years between 1890 and 1918. Many preventive measures were introduced to deal with the spread of typhoid but these varied between the 3 countries, depending largely on their political traditions. Inoculation was particularly successful in preventing typhoid and greatly reduced the number of casualties from this disease during the First World War. Despite this, it proved difficult to prevent paratyphoid infection, and debates continued over which vaccines to use and whether or not immunization should be voluntary. CONCLUSIONS: By the end of the First World War, the value of inoculation in preventing the spread of typhoid had been proven. Its successful implementation demonstrates the importance of vaccination as a public health intervention during times of conflict and social upheaval.
Gesehen am 14.05.2021